A Systematic Review on Demand Response Role Toward Sustainable Energy in the Smart Grids-Adopted Buildings Sector - Al-Ghaili A.M.; Ibrahim Z.-A.B.; Bakar A.A.; Kasim H.; Al-Hada N.M.; Jorgensen B.N.; Hassan Z.B.; Othman M.; Kasmani R.M.; Shayea I. (Institute of Electrical and Electronics Engineers Inc., 2024)
In the so near future, climate change caused by Carbon dioxide (CO2) emissions as a result of an increase in energy demand (ED) in the buildings sector becomes really hazard to our green environment. Both climate change and increase in ED are affected by each other. Such increase in ED would increase both climate change and global warming. Fortunately, there is, however, still plenty of time to address this issue. This increase might be significantly and effectively controlled. One of the effective solutions is to apply demand response (DR) strategies exploiting the smart grid (SG). Hence, SG contributes to help reduce both ED and CO2 emissions. Of importance is establishing SGs-adopted buildings in which DR role could act as an operating and management system aiming to reach energy sustainability. We review researches on DR strategies and technologies applied to SGs-adopted buildings. Unlike previous literature reviews considering certain types of buildings or strategies which therefore narrow the focus of review papers, this review has analyzed numerous types of buildings and a variety of technologies to expand the review's scope. Concluded remarks, insights, challenges faced by researchers, and suggestions proposed by this review paper have been in detail discussed. Limitations, further gaps in future research on DR strategies, potential implications of DR in SG-adopted buildings have been also discussed. Towards sustainable energy in the buildings sector utilizing DR strategies, points of strength and weakness concluded from the reviewed articles have been highlighted and discussed to open trends that might potentially enhance future proposed DR strategies applied to SG-adopted buildings. 2013 IEEE.